What Is Chinese About Chinese Business? Implications for U.S. Responses to China's Rise - Chengxin Pan (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2007)
There has been a commonly held belief, especially in the United States, that Chinese business is distinctively Chinese. Understanding its Chineseness in unitary, monolithic and national terms, this assumption has both underpinned a zero-sum perspective on U.S.-China relations, and fuelled the China threat argument. This paper seeks to critically examine this essentialist construction of Chinese business and its foreign policy implications. Drawing on a global production network (GPN) approach, the paper argues that as well as exhibiting its Chinese characteristics, Chinese business is increasingly characterised by its transnationalness, which calls into question the coherence and unity of the Chinese economy. In this context, the American construction of China as a singular, threatening economic entity not only fails to capture the multiple, unstable identities of Chinese business and the complexities of U.S.-China relations associated with them, but often serves to inform simplistic, counter-productive and even dangerous China policy in the age of global interdependence.
hdl:10398/7412
Keywords: 330; chineseness; chinese business; transnationalness; u.s.-china relations; global production networks